Structure function and engineering of multifunctional non-heme iron dependent oxygenases in fungal meroterpenoid biosynthesis - Yu Nakashima (Nature Portfolio, 2018)
Non-heme iron and α-ketoglutarate (αKG) oxygenases play a major role in fungal meroterpenoid biosynthesis, but their mechanism remains elusive. Here the authors present crystal structures of two oxygenases, AusE and PrhA, which provide insights into the multifunctional nature of these enzymes.